The Baweanese diasporic tradition and its role in spreading the tarekat in Singapore - Yon Machmudi (Cogent Arts & Humanities)
The wandering activity (ngoker lange) has been undertaken in the past and continues to be practiced even today by Baweanese people, both for economic and religious purposes. Through the ngoker lange tradition, the practice of Sufi order(tarekat), spread to Singapore. This article aims to analyze how the diasporic tradition of Bawean people contributed to the the development of the tarekat institution named Tarekat Qadiriyah wan Naqsyabandiyah (TQN) in Singapore. In this study, I employed an interdisciplinary method that utilizes a historical and cultural approach. Data are collected through literature research, direct observations, and interviews with Bawean people in the island and Singapore. This study found that the Bawean diaspora played an important role in spreading tarekat in Singapore. Kiai Usman Al-Ishaqy (1915-1984) and Kiai Mohd Hassan Ash’ari bin Mustafa al-Bakri (1921-2007) were the famous personalities who were instrumental in developing tarekat in Singapore.